The Efficiency of Australian Schools: A Nationwide Analysis Using Gains in Test Scores of Students as Outputs1. Issue 3 (1st August 2016) - Nghiem, Son; Nguyen, Ha Trong; Connelly, Luke B.
Abstract : This study examines the efficiency of schools in Australia and its determinants using the gain in NAPLAN test scores of students in 6, 774 schools in 2009–2011. The results show that, based on empirical input–output combinations, the growth of NAPLAN test scores in Australian schools could be improved by 64 per cent by learning from best practice, on average. At the primary level, Catholic and independent schools are less efficient than public schools. At the secondary school level, though, public schools are found to be less efficient than other (non‐public) schools.